Globalization and civilizations - Mozaffari, Mehdi (Routledge, 2002)
Uniquely, critically interrogates the concept of 'civilization' by asking whether it is still valid in the globalized world economy of the twenty-first century. Includes case studies on the Arab world, Islam, China and Japan.